Interaksi Senyawa Taxifolin dari Buah Kasturi (Mangifera casturi) sebagai Antikanker Payudara: Evaluasi Docking Molekular - Rabiatul Adawiyah; Noer Komari (Universitas Lambung Mangkurat, 2021)
Taxifolin also called dihydroquercetin is a flavonoid. Taxifolin is included in the flavonol subclass and polyphenol class. Taxifolin has been found in the leaves, bark and flesh of Mangifera casturi. Taxifolin is thought to have potential as an antibreast cancer through its activity as an anti-neoplastic agent. The occurrence of breast cancer begins with overexpression of the Human Epidermal Growth Factor Receptor 2 (HER-2) protein which can induce dimerization and autophosphorylation of the tyrosine kinase enzyme, resulting in migration and metastasis of breast cancer cells. This study aims to determine the interaction of taxifolin with HER-2 protein by molecular docking. Molecular docking using the SwissDock web server. Parameters of molecular docking include Gibbs free energy and interaction of taxifolin ligands and HER-2 residues. The results of docking molecular expressed by free energy Gibbs of taxifolin compounds with HER-2 protein is -7,99 kcal / mol, while the free energy Gibbs of the native ligand bond with HER-2 protein is -10.76 kcal / mol. The residues on HER-2 that interacts with taxifolin are GLY727, GLY804, LEU726, THR798, ASP863, ALA730, SER728, ARG849, GLY729, CYS805, THR862, VAL734, LEU852, LYS753, ALA751, ASP808, ARG849, ASN850. The value of Gibbs free energy and the interaction of residues indicate that taxifolin compounds have potential as anticancer breasts. Taxifolin as an inhibitor of HER-2 protein expression.